Modeling early stage atherosclerosis in a primary human vascular microphysiological system - Xu Zhang (Nature Portfolio, 2020)
Human microphysiological systems (MPS) have some advantages over animal models to study the mechanisms of disease. Here the authors use a tissue-engineered blood vessel MPS to create a model of early stage atherosclerosis and assess the effect of several drugs.